Recent Progress in Chemo-Enzymatic Methods for the Synthesis of N-Glycans - Chao, Qiang; Ding, Yi; Chen, Zheng-Hui; Xiang, Meng-Hai; Wang, Ning; Gao, Xiao-Dong (Frontiers in Chemistry, 2020)
Abstract Asparagine (N)-linked glycosylation is one of the most common co- and post-translational modifications of both intra- and extracellularly distributing proteins, which directly affects their biological functions, such as protein folding, stability and intercellular traffic. Production of the structural well-defined homogeneous N-glycans contributes to comprehensive investigation of their biological roles and molecular basis. Among the various methods, chemo-enzymatic approach serves as an alternative to chemical synthesis, providing high stereoselectivity and economic efficiency. This review summarizes some recent advances in the chemo-enzymatic methods for the production of N-glycans, including the preparation of substrates and sugar donors, and the progress in the glycosyltransferases characterization which leads to the diversity of N-glycan synthesis. We discuss the bottle-neck and new opportunities in exploiting the chemo-enzymatic synthesis of N-glycans based on our research experiences. In addition, downstream applications of the constructed N-glycans, such as automation devices and homogeneous glycoproteins synthesis are also described.